Development of a united-atom force field for 1-ethyl-3-methylimidazolium tetracyanoborate ionic liquid - Koller, Thomas Manfred; Ramos, Javier; Garrido, Nuno M.; Fröba, Andreas Paul; Economou, Ioannis G. (Molecular Physics, 2012)
Three united-atom (UA) force fields are presented for the ionic liquid 1-ethyl-3-methylimidazolium tetracyanoborate, abbreviated as [EMIM](+)[B(CN)(4)](-). The atomistic charges were calculated based on the restrained electrostatic potential (RESP) of the isolated ions (abbreviated as force field 1, FF-1) and the ensemble averaged RESP (EA-RESP) method from the most stable ion pair configurations obtained by MP2/6-31G*+ calculations (abbreviated as FF-2 and FF-3). Non-electrostatic parameters for both ions were taken from the literature and Lennard-Jones parameters for the [B(CN)(4)](-) anion were fitted in two different ways to reproduce the experimental liquid density. Molecular dynamics (MD) simulations were performed over a wide temperature range to identify the effect of the electrostatic and non-electrostatic potential on the liquid density and on transport properties such as self-diffusion coefficient and viscosity. Predicted liquid densities for the three parameter sets deviate less than 0.5% from experimental data. The molecular mobility with FF-2 and FF-3 using reduced charge sets is appreciably faster than that obtained with FF-1. FF-3 presents a refined non-electrostatic potential that leads to a notable improvement in both transport properties when compared to experimental data.
Keywords: electrostatic potential; force field development; ionic liquids; tetracyanoborate; united-atom model